2016
DOI: 10.1158/1055-9965.epi-15-1294
|View full text |Cite
|
Sign up to set email alerts
|

Missing the Target for Routine Human Papillomavirus Vaccination: Consistent and Strong Physician Recommendations Are Lacking for 11- to 12-Year-Old Males

Abstract: Background Rates of routine human papillomavirus (HPV) vaccination of adolescent males in the U.S. are low. Leading health organizations advocate consistent and strong physician recommendations to improve HPV vaccine dissemination. This study describes the prevalence and correlates of consistent and strong physician recommendations for HPV vaccination of adolescent males. Methods We surveyed pediatric and family medicine physicians in Florida about their HPV vaccine recommendations for male vaccine-eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 45 publications
(44 reference statements)
3
40
1
Order By: Relevance
“…Professional organizations recommended consistent and strong provider recommendation for HPV vaccine [28, 29] as a primary approach to improving HPV vaccination. However, reported elsewhere [23], only 30.6% of physicians in this study strongly and consistently recommended HPV vaccination for males ages 11–12. Yet few studies explored messages promoting HPV vaccination for physicians to use with parents.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Professional organizations recommended consistent and strong provider recommendation for HPV vaccine [28, 29] as a primary approach to improving HPV vaccination. However, reported elsewhere [23], only 30.6% of physicians in this study strongly and consistently recommended HPV vaccination for males ages 11–12. Yet few studies explored messages promoting HPV vaccination for physicians to use with parents.…”
Section: Discussioncontrasting
confidence: 59%
“…Participant recruitment and the survey instrument are described in detail elsewhere [23, 24] and are summarized below.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, vaccine uptake may increase if physicians are provided with other strategies or materials to use in conjunction with fact sheets, such as client and provider reminders [14]. However, as previously reported, only 31% of providers in the current study indicated using any reminders, suggesting a substantial area for improvement [10]. Furthermore, most physicians in our study (regardless of specialty) indicated a preference for CDC materials in stark contrast to the very low preferences for materials from professional organizations.…”
Section: Discussionmentioning
confidence: 83%
“…Participant recruitment and the survey are detailed elsewhere [10, 11] and briefly summarized below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation